2008
DOI: 10.1029/2007gb003077
|View full text |Cite
|
Sign up to set email alerts
|

Climatically driven loss of calcium in steppe soil as a sink for atmospheric carbon

Abstract: During the last several thousand years the semi‐arid, cold climate of the Russian steppe formed highly fertile soils rich in organic carbon and calcium (classified as Chernozems in the Russian system). Analysis of archived soil samples collected in Kemannaya Steppe Preserve in 1920, 1947, 1970, and fresh samples collected in 1998 indicated that the native steppe Chernozems, however, lost 17–28 kg m−2 of calcium in the form of carbonates in 1970–1998. Here we demonstrate that the loss of calcium was caused by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…The region's subsoils have also lost Ca 2+ , which was present as calcium carbonate over the past 100 years, which has been linked to the trend in increasing precipitation (Lapenis et al, 2008). It is considered likely that calcium is involved in stabilization reactions with BC (Czimczik and Masiello, 2007), and there is circumstantial evidence that the loss of calcium from soil is associated with the loss of BC (Clough and Skjemstad, 2000).…”
Section: K Hammes Et Al: Centennial Black Carbon Turnovermentioning
confidence: 99%
“…The region's subsoils have also lost Ca 2+ , which was present as calcium carbonate over the past 100 years, which has been linked to the trend in increasing precipitation (Lapenis et al, 2008). It is considered likely that calcium is involved in stabilization reactions with BC (Czimczik and Masiello, 2007), and there is circumstantial evidence that the loss of calcium from soil is associated with the loss of BC (Clough and Skjemstad, 2000).…”
Section: K Hammes Et Al: Centennial Black Carbon Turnovermentioning
confidence: 99%
“…To date, an extensive experimental material has been accumulated in the early literature on the amount of leachable calcium from the soils because of washing (Lapenis, 2008;Youngil et al, 2009;Adomaitis et al, 2013). It was found that the washout intensity depends on the initial calcium content in the soils, the amount of precipitation, the granulometric composition of soils, the dose of the applied ameliorant, the amount of fertilizer used, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such uptake would not occur in dry soils; thus, the extrapolated amounts are likely much too high. Carbon dioxide associated with carbonate dissolution accounted for an uptake of 2.1 to 7.4 g C m −2 yr −1 in a semi‐arid, Russian cold steppe ecosystem (Lapensis et al , 2008)…”
mentioning
confidence: 99%